1998
DOI: 10.1098/rspb.1998.0416
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation between parapatric ‘nearshore’ and ‘offshore’ populations of the bottlenose dolphin

Abstract: The existence of nearshore and o¡shore populations of the bottlenose dolphin has been documented throughout its range. In several cases the two regional forms have been shown to be morphologically distinct, although there is considerable overlap for most characters. The populations o¡ the eastern coast of North America have been the subject of a long-term programme of research on their distribution and movements. In this study, we compare mitochondrial and nuclear genetic markers between dolphins classi¢ed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
212
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(224 citation statements)
references
References 17 publications
12
212
0
Order By: Relevance
“…Top predators can drive diversification of prey 20,21 and help maintain biodiversity 22 . It is typically assumed that apex predators display little phenotypic variation, but there is emerging evidence for rich phenotypic diversity and ecotype formation of predators at the top of multiple food webs 23,24 . Yet, the factors promoting this diversity are largely unknown, perhaps because studying large top predators is very difficult on any scale smaller than the whole ecosystem.…”
mentioning
confidence: 99%
“…Top predators can drive diversification of prey 20,21 and help maintain biodiversity 22 . It is typically assumed that apex predators display little phenotypic variation, but there is emerging evidence for rich phenotypic diversity and ecotype formation of predators at the top of multiple food webs 23,24 . Yet, the factors promoting this diversity are largely unknown, perhaps because studying large top predators is very difficult on any scale smaller than the whole ecosystem.…”
mentioning
confidence: 99%
“…Also, the dorsal fin is the only appendage that is constantly exposed to 63 ambient air, and thus is subject to different thermoregulatory conditions from the rest of the body 64 Westgate et al, 2007;Barbieri et al, 2010). (Walker, 1981; 68 Vidal, 1993;Gao et al, 1995;Goodwin et al, 1996;Hoelzel et al, 1998; Turner and Worthy, 69 1998;. Polyphenisms in traits whose functions arose as adaptations to new life 70 conditions (e.g.…”
mentioning
confidence: 99%
“…in Tursiops sp. : Hoelzel et al 1998b;Krützen et al 2004). Even though it was not possible to obtain reliable estimates of the amount of gene flow, our results indicated that gene flow was sufficient to prevent differentiation within and between archipelagos in common and spotted dolphins at the scale of the study area.…”
Section: Absence Of Population Structure Within and Between Archipelagosmentioning
confidence: 99%
“…Fourteen polymorphic dinucleotide microsatellite loci were analysed: d08, d22 (Shinohara et al 1997), EV14, EV37 Amos 1996), FCB1, FCB17 (Buchanan et al 1996), Kwm2a, Kwm12a, Kwm9b (Hoelzel et al 1998b), Mk6, Mk8 (Krützen et al 2001), Sw10, Sw19 (Richard et al 1996) and TexVet5 (Rooney et al 1999). Loci TexVet5 and Kwm2a were not analysed in S. frontalis because they failed to amplify.…”
Section: Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation